THE SIGNIFICANCE OF USING METHODOLOGICAL GAMES IN TEACHING A SECOND LANGUAGE IN THE PRESCHOOL EDUCATION SYSTEM - Kasimova Shahlo Bahromovna (American Journals, 2023)
In this article, some comments are made about the pedagogical conditions of using methodical games in the teaching of a second language in the preschool education system and its importance in today's pedagogical system. Also, the article gives examples of some methodical games and describes the processes of their implementation.
Keywords: Methodical games, educator, future, second language, fairy tale, children, speech development, conditions.